PENGARUH THINK PAIR SQUARE TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Tesa Meisiska (Jurnal Edukasi dan Penelitian Matematika, 2018)
Learning process that is implemented in SMPN 16 Padang was still not optimal to improve students' mathematics learning outcomes. The process of learning mathematics at SMPN 16 Padang is still centered on teachers and students tend to passively receive learning. One alternative to improve learning outcomes is to apply cooperative learning of Think Pair Square (TPSq) type in learning mathematics. Purpose of this study is to determine whether the results of learning mathematics students learning applying cooperative learning model Think Pair Square type better than the student learning outcomes with conventional learning by applying the model of cooperative learning type TPSq on students of class VIII SMPN 16 Padang. This research was a quasi-experiment, with Static Group Design. Population were student in grade VIII at SMPN 16 Padang. The research sample was chosen randomly and elected VIII.4 as experimental class and VIII.6 as control class. The results of this study indicate the results of learning mathematics students who learn to use cooperative learning model with TPSq’s type better than student who learned used conventional learning.Keywords – cooperative learning, result of learning mathematical, think pair square